Study on Bank Employee Retention Strategies: Comparative Analysis of Retention Strategies in Public and Private Banks (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Employee retention is a major challenge for modern businesses. This issue has repercussionsin the financial industry as well. The study's primary objectives were to gain an understanding of, evaluate,and compare the retention strategies employed by the participating institutions. Two public banks (PNBand Canara Bank) and two private banks (ICICI Bank and YES Bank) were considered in the study. Thisstudy's overarching objective is to dissect the retention practises of commercial and governmentfinancial institutions to highlight their disparities. The banking industry has introduced numerousground-breaking programmes in the areas of professional development, pay and benefits, retirementplanning, and evaluation of employee performance, among others.